2004
DOI: 10.1128/aac.48.5.1872-1875.2004
|View full text |Cite
|
Sign up to set email alerts
|

Disposition and Metabolic Profiles of [ 14 C]Viramidine and [ 14 C]Ribavirin in Rat and Monkey Red Blood Cells and Liver

Abstract: The disposition and metabolic profiles of [14 C]viramidine and [ 14 C]ribavirin were compared in rat and monkey red blood cells and liver. Our data reveal that the total ribavirin-related components (ribavirin plus its mono-, di-, and triphosphate metabolites) may account for most of the drug in monkey liver following prolonged oral administration of viramidine.Ribavirin is a purine nucleoside analog ( Fig. 1) with broadspectrum activity against a variety of DNA and RNA viral infections (17,19). In combination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…have been reported for the determination of ribavirin in biological matrices [24][25][26][27][28][29][30][31][32][33][34]. However, separate methods using HPLC-UV or HPLC with radioactivity detection were used for the measurement of ribavirin base in these samples [22,31,34]. To our best knowledge, only a few HPLC-UV methods are available for the quantification of both ribavirin and ribavirin base in biological samples [35,36].…”
Section: Ribavirinmentioning
confidence: 98%
See 1 more Smart Citation
“…have been reported for the determination of ribavirin in biological matrices [24][25][26][27][28][29][30][31][32][33][34]. However, separate methods using HPLC-UV or HPLC with radioactivity detection were used for the measurement of ribavirin base in these samples [22,31,34]. To our best knowledge, only a few HPLC-UV methods are available for the quantification of both ribavirin and ribavirin base in biological samples [35,36].…”
Section: Ribavirinmentioning
confidence: 98%
“…The first pathway is a reversible phosphorylation in nucleated cells [10,21,22], and the second is degradation involving deribosylation and/or amide hydrolysis [10,22]. As the result of deribosylation, ribavirin is biotransformed to ribavirin base (1,2,4-triazole-3-carboxamide) [10,22]. In healthy adults, it is estimated that approximately 30-55% of inhalated ribavirin was excreted as ribavirin base in urine within 72-80 h, and about 50% of orally administered ribavirin was excreted as ribavirin base within 24 h [10].…”
Section: Ribavirinmentioning
confidence: 99%
“…Pharmacokinetic analysis of ribavirin administered to animals indicated that most of the ribavirin is degraded and excreted from urea. Of the remaining drug that is distributed around various parts of the animal, a significant amount exists in the form of triazole nucleobase (3,4). Inhibiting ribavirin phosphorolysis represents a logical strategy to enhance the drug's stability, thereby delivering more active metabolites for efficacy.…”
mentioning
confidence: 99%
“…Taribavirin contains a positively charged 3-carboxymide group [12] and is poorly taken up by red blood cells (RBCs). The concentration of taribavirin-derived ribavirin found in RBCs is half that of ribavirin after oral dosing [14]. Higher RBC ribavirin levels correlate with greater decreases in hemoglobin secondary to hemolysis [15], so combination therapy with taribavirin plus pegylated interferon may be associated with a lower incidence of treatment (ribavirin)-related anemia.…”
Section: Introductionmentioning
confidence: 99%
“…Taribavirin is preferentially taken up by the liver and is likely converted to ribavirin by hepatic adenosine deaminase [13,14]. Taribavirin-derived ribavirin accumulates in the liver at three times the rate of native ribavirin [14].…”
Section: Introductionmentioning
confidence: 99%